Enhancing the multi-attribute method through an automated and high-throughput sample preparation - Pongkwan Sitasuwan; Thomas W. Powers; Tiffany Medwid; Yuting Huang; Bradley Bare; L. Andrew Lee (mAbs, 2021)
The multi-attribute method (MAM), a recent advance in the application of liquid chromatography-mass spectrometry within the pharmaceutical industry, enables the simultaneous monitoring of multiple product quality attributes in a single analytical method. While MAM is coupled with automated data processing and reporting, the sample preparation, based on proteolytic peptide mapping, remains cumbersome and low throughput. The standard sample preparation for MAM relies on protein denaturation, reduction, and alkylation prior to proteolytic digestion, but often a desalting step is required to maintain enzymatic activity. While most of the sample preparation can be automated on a standard robotic liquid handling system, a streamlined approach for protein desalting and temperature modulation is required for a viable, fully automated digestion. In this work, for the first time, a complete tip-based MAM sample preparation is automated on a single robotic liquid handling system, leveraging a deck layout that integrates both heating and cooling functionalities. The fully automated method documented herein achieves a high-throughput sample preparation for MAM, while maintaining superior method performance.Abbreviations: MAM: multi-attribute method; PQAs: product quality attributes; CE: capillary electrophoresis; IEX: ion-exchange chromatography; HILIC-FLR: hydrophilic interaction liquid chromatography coupled to a fluorescence detector; RP-LC/UV: reversed-phase liquid chromatography coupled to a UV detector; MS: mass spectrometry; NPD: new peak detection; GdnHCl: guanidine hydrochloride; TIC: total ion current; pAb: polyclonal antibody; IgG: immunoglobulin G; DTT: dithiothreitol; IAA: iodoacetic acid; TFA: trifluoroacetic acid; A280: absorbance at 280 nm wavelength; 96MPH: 96-channel multi-probe head; CPAC: Cold Plate Air Cooled; HHS: Hamilton Heater Shaker; DWP: Deep-Well Plate; PCR: Polymerase Chain Reaction; NTR: Nested Tip Rack; Met: methionine; Trp: tryptophan; N-term pQ: N-terminal glutamine cyclization; Lys: lysine; PAM: peptidylglycine α-amidating monooxygenase; G0F: asialo-, agalacto-, bi-antennary, core substituted with fucose; G1F: asialo-, mono-galactosylated bi-antennary, core substituted with fucose; G2F: asialo-, bi-galactosylated bi-antennary, core substituted with fucose; G0: asialo-, agalacto-, bi-antennary; Man5: oligomannose 5; Man8: oligomannose 8; TriF: asialo-, tri-galactosylated tri-antennary, core substituted with fucose.